Análise sócio-ambiental do segmento do baixo curso do rio Maranguapinho na cidade de Fortaleza-Ce: relações sociedade x natureza - Sales, Luiz Belino Ferreira (2004)
The Environmental Analysis of low course Maranguapinho-Ce River, constitutes a work of understanding of the present complexities in the area through the evaluation of the impacts of the use process and occupation of the earth and his/her effect in the ecology of the landscape and the partner-environmental resultants of such actions. The work search an integrated approach using for that elements of understanding of the dynamics of formation of the active natural processes and of the present social processes in the study area. His/her importance consists of the understanding of the landscape as a space unit, an operational concept (SUERTEGARAY, 2000), that it is formed of the synthesis of the natural processes with the social processes. The studied area understands a segment of the bass course of the river located Maranguapinho in the city of Fortaleza in his/her portion west, being understood among the neighborhoods Antônio Bezerra, Autran Nunes, Henrique Jorge, Parque Genibaú and João XXIII.